The importance of implementing good aquaculture practices based on the analysis of Qur’anic verses - Kartika, Betania; Perdana, Firdaus Fanny Putera (2019)
The objectives of the papers include presenting the current conditions of aquaculture practices, understanding the importance of good aquaculture practices and most importantly reviewing the Quranic verses in accordance with the importance to conduct good aquaculture practices. The aquaculture itself is in charge of around 47 per cent of the fish consumption in the world. Its value is estimated to be around 125 billion USD and it is responsible for 13% of the world’s animal-source protein (eggs and dairy excluded). Around 24 million people rely on the sustainability of aquaculture to ensure they have a proper living. The Quranic verses state about environmental corruption, prohibition of wastefulness and the importance in ensuring the environment to be well protected. It is crucial that humans start to carefully monitor the environment as what happens to it is derived from their actions, as stated in Quránic verse 30:41: “Mischief has appeared on the land and sea because of (the meed) that the hands of men have earned.” The paper also discusses the importance of productivity and quality as aspects to achieve success. The method used is the library research which includes the observation from Islamic perspectives. This is in line with achieving the highest objectives of Shariah, which protect the farmers, the environment, the aquaculture and the consumers. The output of the study may serve MyGAP and MS 1500:2009.